Peran, Organisasi, dan Kekayaan Kearifan Lokal dalam Keberlanjutan Sosial Ekonomi Perikanan Tradisional (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2025)
This article discusses how the role of the community, local organizational structures, and the values of local wisdom contribute to supporting socio-economic sustainability within the traditional fisheries sector. By examining the practical implementation in several Indonesian coastal communities, this article reveals the uniqueness of traditional practices that not only sustain economic livelihoods but also maintain social and ecological harmony. This study utilizes a descriptive qualitative approach incorporating case studies and in-depth interviews with key stakeholders. The results demonstrate that preserving local wisdom by strengthening community organizations serves as a key factor for sustainable innovation in this sector.